2019
DOI: 10.1080/19932820.2019.1595955
|View full text |Cite
|
Sign up to set email alerts
|

Serum paraoxonase (a high-density lipoprotein-associated lipophilic antioxidant) activity in clinical follow-up of patients with acute pancreatitis, with particular emphasis on oxidative stress parameters and lipid profile: a prospective pilot trial

Abstract: (2019) Serum paraoxonase (a high-density lipoprotein-associated lipophilic antioxidant) activity in clinical follow-up of patients with acute pancreatitis, with particular emphasis on oxidative stress parameters and lipid profile: a prospective pilot trial,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Previous studies show that patients with severe acute pancreatitis are often accompanied by hypocholesterolemia [12,50]. Regarding the lipid profile status in acute pancreatitis, a decrease in HDL level has been reported; an abnormal lipid profile may have a role in the pathogenesis of acute pancreatitis in which HDL-associated antioxidant defense is impaired [51]. In this study, it was shown that the decrease in HDL-C levels is a clinical indicator with possible predictive capacity, with a comparable diagnosis in the analysis of significant ROC curves (p < 0.004) and an AUC > 0.750 with a cut-off point of 28.5 mg/dL for MOF, which was maintained from admission to 48 h of hospital stay in the ED (Figure 1B,D).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that patients with severe acute pancreatitis are often accompanied by hypocholesterolemia [12,50]. Regarding the lipid profile status in acute pancreatitis, a decrease in HDL level has been reported; an abnormal lipid profile may have a role in the pathogenesis of acute pancreatitis in which HDL-associated antioxidant defense is impaired [51]. In this study, it was shown that the decrease in HDL-C levels is a clinical indicator with possible predictive capacity, with a comparable diagnosis in the analysis of significant ROC curves (p < 0.004) and an AUC > 0.750 with a cut-off point of 28.5 mg/dL for MOF, which was maintained from admission to 48 h of hospital stay in the ED (Figure 1B,D).…”
Section: Discussionmentioning
confidence: 99%
“…The impaired anti-inflammatory function might be linked to reduced HDL-C levels in AP leading to increased free fatty acids (FFAs), which produce an acidic microenvironment (Zhang et al, 2017). HDL-C also possesses an antioxidant ability, which is mediated by the paraoxonase-1 activity in AP (Yuksekdag et al, 2019). Notably, the presence of FFAs results from the breakdown of TG including chylomicrons and is associated with HTG AP.…”
Section: Discussionmentioning
confidence: 99%
“…Tvarijonaviciute et al ( 53 ) suggested that PON-1 activity is positively correlated with CRP and triglyceride levels and could be considered as a marker to assess AP severity. Yuksekdag et al ( 54 ) demonstrated that the low levels of PON-1, HDL-C, SOD and TAC identified in the early stages of AP started to increase after treatment with analgesics, antibiotics and enteral/parenteral nutrition, as well as insulin dose adjustment for diabetic patients and personal medication for arterial hypertension. Furthermore, the initially elevated MDA concentrations decreased, thus suggesting that PON-1, SOD and TAC might represent potential markers to evaluate the clinical course of the disease.…”
Section: Antioxidants and Oxidative Stressmentioning
confidence: 99%